Perempuan dan Hak Asasi Manusia dalam Lensa Filsafat: Dilema Etika dan Implementasi - Bato, Kamilus (Proceedings of The National Conference on Indonesian Philosophy and Theology, 2024)
Human rights in the context of women through a philosophical lens brings us into deep reflection about the rights, dignity and role of women in society. In philosophy, women are considered as equal individuals to men, eliminating discrimination based on gender. The concepts of bodily autonomy, reproductive rights, and protection against violence are at the center of ethical and moral debates about women's human rights. Philosophical thinking also emphasizes that women have an active role in raising social and political awareness to achieve gender equality. This involves the moral responsibility and collective action of women in fighting for their rights. Through a philosophical lens, understanding women's human rights encourages us to see women not only as objects receiving rights, but also as subjects who are empowered to shape a more just future. Therefore, the philosophy provides a strong foundation for advocacy for gender equality and social change that is more inclusive and has equal rights to live with dignity and freedom.AbstrakHak asasi manusia dalam konteks perempuan melalui lensa filsafat membawa kita ke dalam refleksi mendalam tentang hak, martabat, dan peran perempuan dalam masyarakat. Dalam filsafat, perempuan dianggap sebagai individu yang setara dengan laki-laki, menghapuskan diskriminasi berdasarkan jenis kelamin. Konsep otonomi tubuh, hak reproduksi, dan perlindungan terhadap kekerasan menjadi pusat perdebatan etis dan moral tentang HAM perempuan. Pemikiran filsafat juga menekankan bahwa perempuan memiliki peran aktif dalam menggugah kesadaran sosial dan politik untuk mencapai kesetaraan gender. Ini melibatkan tanggung jawab moral dan aksi kolektif perempuan dalam memperjuangkan hak-hak mereka. Melalui lensa filsafat, pemahaman tentang HAM perempuan mendorong kita untuk melihat perempuan bukan hanya sebagai objek penerima hak, tetapi juga sebagai subjek yang berdaya untuk membentuk masa depan yang lebih adil. Oleh karena itu, filsafat memberikan fondasi yang kuat untuk advokasi kesetaraan gender dan perubahan sosial yang lebih inklusif dan memiliki hak yang sama untuk hidup dengan martabat dan kebebasan.